Evaluasi Efektivitas Pembelajaran Multidisiplinier di MIIT Nurul Iman Punung - Saputra, Dona Adi Bayu; Tobroni, Tobroni; Faridi, Faridi (TSAQOFAH, 2024)
Education as a foundation for character building and increasing the potential of human resources requires an innovative approach in the learning process. One approach that is developing is multidisciplinary learning, which aims to integrate various disciplines in one learning framework. This study evaluates the effectiveness of applying multidisciplinary learning methods in Madrasah Ibtidaiyah Islam Terpadu (MIIT) Nurul Imam Punung, focusing on improving academic achievement and developing students' skills holistically.